2021
DOI: 10.1097/qai.0000000000002737
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Young Age and Sex Work Are Associated With HIV Seroconversion Among Transgender Women in São Paulo, Brazil

Abstract: Background: Transgender women worldwide have the highest prevalence of HIV and the lowest access to prevention among groups at risk of HIV. However, few longitudinal studies have directly measured HIV incidence and identified predictors of HIV acquisition among transgender women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…In a study carried out in Rio de Janeiro, with about 322 trans women, aged between 25 and 39 years, it was identified that 54%, equivalent to 174 women, were infected with HIV, about 62% were low-income and had intense sex work, which in part explains the occurrence of 46.3% and 54% of sexual and physical violence, respectively. [15] Veras and collaborators [2021] [16] cite prostitution as one of the main causes of seroconversion in trans women, especially between the ages of 18 and 24 years. The social vulnerability of sex professionals also provides situations that lead to sex without a condom, such as rape, extra payment for unprotected sex or the feeling of security and trust with stable partners, [17] as well as the frequent practice of anal sex, which is also a high risk factor for HIV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out in Rio de Janeiro, with about 322 trans women, aged between 25 and 39 years, it was identified that 54%, equivalent to 174 women, were infected with HIV, about 62% were low-income and had intense sex work, which in part explains the occurrence of 46.3% and 54% of sexual and physical violence, respectively. [15] Veras and collaborators [2021] [16] cite prostitution as one of the main causes of seroconversion in trans women, especially between the ages of 18 and 24 years. The social vulnerability of sex professionals also provides situations that lead to sex without a condom, such as rape, extra payment for unprotected sex or the feeling of security and trust with stable partners, [17] as well as the frequent practice of anal sex, which is also a high risk factor for HIV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Several alternatives improve access to treatment among the HIV-positive population in Latin America, including Peru [16][17][18]. Cessation of treatment of newly diagnosed PLWHA in Peru is still high, especially considering the transgender population and MSM, who represent about 70% of newly diagnosed cases [19].…”
Section: Discussionmentioning
confidence: 99%
“…Under half of participants were able to attend four in-person sessions or more and maintain monthly communication for 4 months. Such findings are not new; studies have consistently found that the many structural inequities and challenges faced by transgender women, such as shortages of housing, money for transportation, or food or other basic needs, make it difficult to attend program and research visits [ 20 , 58 ]. Adherence to the navigation program was particularly low among younger participants and among those without stable housing, suggesting multiple vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…From May to November 2018, TWH age 18 and over were recruited from the CRT testing and treatment center, through community-based outreach, and from among participants testing HIV-positive in the Transnational cohort [ 36 ]. The Transnational Cohort Study was a longitudinal cohort of transgender women recruited through respondent-driven sampling (RDS); 545 participants were followed for just over 2 years, including biannual surveys and HIV testing in order to establish incidence [ 37 ]. Participants testing positive or sero-converting in the Transnational study were referred to TransAmigas.…”
Section: Methodsmentioning
confidence: 99%